Analisis Sejarah dan Perkembangan Perkeretaapian di Jepang - Syuhada, Farrell Hamzah; Putri, Oktaviana (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 1 (2023), 2023)
This research discusses the history of Japanese railways and the factors causing the progress of railways in Japan. The research method used in this research is descriptive qualitative. The data collection technique used in this research is a literature study or literature review. The data in this research were taken from journals, books, documentation, internet and literature that discussed the topic being researched. The results of this study are the history of Japanese railways starting in 1872 at the beginning of Japan's new era, namely the Meiji era. Japan learned the rail system from England. Initially, the railroads in Japan were under the auspices of one company, namely JNR, due to go into liquidation, Japan was forced to make JNR a private company, JNR changed its name to JR and is divided into 9 companies to this day. While the factor for the advancement of Japanese railways is Japan's long experience in the world of railways, which is more than 150 years, Japan dares to take risks in the development of railways, Japan is able to overcome competition with private railroad companies, and finally, the Japanese people are disciplined and punctual.